Feminist Research Methodology: Making Meanings of Meaning-Making, 1st edition - Wickramasinghe, Maithree (Routledge, 2020)
This book focuses on feminist research methodology, exploring and analysing its constituting methods, theory, ontology, epistemology, ethics and politics, and research issues relating to women, gender and feminism in Sri Lanka. The book examines ways of meaning-making for the political, ideological and ethical purposes of promoting individual and social change, and constructs an example of feminist research praxis.